Suprasellar colloid cyst: An unusual location - Paniraj; Panigrahi; Reddy; Satish (Journal of Medical and Scientific Research, 2013)
Background: Colloid cysts are rare intracerebral lesions that are preferentially encountered within the third ventricle. There are only a few reports in which colloid cysts are described in other locations such as the fourth ventricle, brainstem, cerebellum and suprasellar region.